2004
DOI: 10.1177/0115426504019006640
|View full text |Cite
|
Sign up to set email alerts
|

Determining Feeding Tube Location by Gastric and Intestinal pH Values

Abstract: The pH value was a reliable predictor of nasoduodenal tube placement. However, radiographic confirmation of location could not be excluded because of the low sensitivity using pH measurements alone. An increase of > or = 1.0 in gastric vs intestinal pH specimens could be useful to determine use of radiography confirmation of tube placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
(9 reference statements)
3
13
1
Order By: Relevance
“…The mean gastric pH for all subjects was found to be 4·2 (SD 1·20). This result is similar to the result [4·8 (SD 2·3)] of a study by Phang et al. (2004).…”
Section: Discussionsupporting
confidence: 92%
“…The mean gastric pH for all subjects was found to be 4·2 (SD 1·20). This result is similar to the result [4·8 (SD 2·3)] of a study by Phang et al. (2004).…”
Section: Discussionsupporting
confidence: 92%
“…A conservative approach was taken in this series given that 78% of patients were on acid-suppressing medications, such that a pH of Յ5 was taken to indicate gastric placement (24). A prepyloric fluid aspirate was only obtained in 60% of all intubations, with only 44% showing a gastric pH Յ5.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pH of aspirates has gained more attention compared to other values, it has some drawbacks in patients receiving acid suppressant drugs or continuous enteral feeding [89,90]. Gilbertson [36] demonstrated that a gastric aspirate pH less than 5 is a safe, reliable and practical cut off level in paediatric patients.…”
Section: Assessment Of Correct Placementmentioning
confidence: 99%